Effects of ground candlenut (Aleurites moluccana (L.) willd.) kernel on growth performance and fatty acid composition in broiler chickens - Abdul Rasid @ Abdul Rashid, Rohaida (2014)
Candlenut (Aleurites moluccana) is a spice commonly used in cooking especially in Indian and Asian recipes. The kernel contain more than 40% oil which is used for industrial purposes especially in paints or as drying oils. The candlenut kernel oil contains high amounts of alpha linolenic fatty acid and linoleic acid, unfortunately, it also contain anti-nutritional factors such as phorbol and saponin. Therefore, it application in animal nutrition especially poultry is limited. The objective of this study was to examine if candlenut kernel can be a source of polyunsaturated fatty acids for poultry and to identify methods of heating to reduce the anti-nutritional factors in the kernel. Three experiments were conducted to determine the effects of ground candlenut (Aleurites moluccana) kernel supplementation on growth performance and fatty acid composition in broiler chickens. In the first experiment, the candlenut kernels were ground to 2 - 3 mm particles and the proximate composition of the kernels was determined. The dry matter, ash, crude fibre, crude protein, ether extract and nitrogen free extract were 94.39%, 1.02%, 4.71%, 23.56%, 65.88% and 4.83%, respectively,whilst gross energy was 32.05 MJ/kg. The oil fraction contained 41.6% linoleic acid,29.5% linolenic acid, 21.6% oleic acid, 4.86% palmitic acid and 2.42% stearic acid. Only 7.74% (fresh weight basis) saponin was detected as anti-nutritional component whilst hydrogen cyanide and phorbol esters were not detected. The total contents of phenol and antioxidants were 127.6 mg/100g and 212.9 mg/100g, respectively. The results indicated that candlenut kernels may be a source of omega-3 fatty acids for broiler chickens and that dietary supplementation may enrich the fatty acids contents in the meat of chickens. Hence, the second experiment was conducted to examine the effect of ground candlenut kernel as a dietary source of omega-3 fatty acids on the growth performance and fatty acid contents in the meat of broiler chickens. A total of 280 male broiler 21-day old chicks (Cobb 500) were used in an experiment to determine the effects of varying levels of ground candlenut kernel supplementation (0, 0.5, 1.0 and 2.0%) in broiler diet on growth performance and carcass characteristics of broiler chickens at grower-finisher stage. In this experiment, supplemented 2% of ground candlenut kernel in broiler diet had significantly (p<0.05) higher final body weight and body weight gain than in control and other levels. Higher mortality rate (8%) in the treatment group (2.0% ground candlenut kernel) could be due to the presence of anti-nutritional factor (saponin). Hence, supplementation of 2% ground candlenut kernel may be producing a better performance if the toxicity could be eliminated or reduced. The last experiment was conducted to determine the effects of heat treated ground candlenut kernel supplementation in broiler diet on growth performance, carcass yield, nutrient digestibility, and fatty acid profiles in meat at grower-finisher stage. A total of 270 male broiler chicks 21 days old (Cobb 500) were divided into six groups and fed diet containing 2% ground candlenut kernel which been heat treated by (a) dry heating, (b) roasting (c) boiling and (d) autoclaving. The group on control diet were given feed without ground candlenut kernel, while the negative control is the diet supplemented with untreated ground candlenut kernel. Although growth performance, carcass yield, nutrient digestibility and fatty acid profiles in meat were significantly (p<0.05) influenced by heat treatment the differences were small. Based on the results,heat treatment by autoclaving showed the best performance amongst the treatments. In conclusion, supplementation of ground candlenut kernel heat-treated by autoclaving in broiler diet showed improved broiler performance and increased fatty acid composition especially omega-3 fatty acids in the meat.